Analysis Of The Mechanical Properties Of Brick With The Addition Of Cotton - Ety Jumiati; Nita Zahara Nasution; Abdul halim Daulay (Universitas Islam Negeri Sumatera Utara Medan, 2020)
AbstractIt has been done making bricks with the addition of cotton.Variations in the mixture of cement, sand and cotton are sample A (30%:70% :0%), sample B (30%:69,5%:0,5%), sample C (30%:69%:1%), sample D (30%:68,5%:1,5%), Water Cement Factor of 0,5 and dry time one day. Characteristic of the tests carried out include: compressive strength and fracture strength.Analysis of the mechanical properties of the bricks produced in sample A with a compressive strength value = 28.81 kg/cm2 and fracture strength value = 23.11kg/cm2, sample B with acompressive strength value = 26.85 kg/cm2 and fracture strength value = 22.32 kg/cm2, sample C with a compressive strength value = 25.10 kg/cm2 and fracture strength value = 15.09 kg/cm2, sample D with a compressive strength of 17.14 kg/ cm2 and a fracture strength value 15.51kg/cm2. The bricks produced namely in sample B.Keywords :Bricks, Cotton, and Cement